Clinical feature and genetic analysis of HMBS gene in Chinese patients with acute intermittent porphyria: a systematic review - Yi Ren; Shuang Li; Jia-Jia Lei; Ru Li; Bai-Xue Dong; Jing Yang (Frontiers in Genetics, 2023)
Background: Early detection and diagnosis are important crucial to prevent life-threatening acute attacks in patients with acute intermittent porphyria (AIP). We aim to provide comprehensive data on the clinical and hydroxymethylbilane synthase (HMBS) gene variant characteristics and genotype-phenotype association of Chinese patients with AIP in order to improve clinicians’ knowledge of AIP and reduce misdiagnosis and mistaken treatment.Methods: We searched the literature on Chinese patients with AIP in PubMed, Web of Science, Wiley Online Library, ScienceDirect and Chinese literature databases up to August 2023 in our analysis to explore the clinical and HMBS gene variant characteristics of Chinese patients with AIP.Results: A total of 41 original articles associated with Chinese AIP patients were included for analysis: 97 variants were detected in 160 unrelated families, including 35 missense, 29 frameshift, 24 splicing and 9 nonsense variants, with c.517C>T being the most common variant. Clinical data were reported in 77 of 160 patients: Most of them were female (67/77) and the age was 28.8 ± 9.9 years. The most common symptom was abdominal pain (73/77, 94.8%), followed by central nervous system symptoms (45/77, 58.4%). 13.0% (10/77) of patients experienced psychiatric symptoms. Hyponatremia was the most common electrolyte abnormality (42/77). 31 patients received carbohydrate loading therapy, and 30 of them were improved. 6 patients were treated with carbohydrate loading combined with hemin therapy and 5 eventually improved. All variants causing premature stop codons, frameshifts or enzyme activity center may experience more severe clinical phenotypes such as seizures, respiratory paralysis, intracranial hemorrhage disorder or respiratory failure.Conclusion: The most common presenting symptom in Chinese AIP patients was abdominal pain, followed by central nervous system symptoms. The HMBS gene analysis in Chinese AIP patients revealed that the heterogeneity is strong and the most common variant was missense mutation, with c.517C>T being the most common variant. The genotype-phenotype association helps guide clinical diagnosis and treatment. However, the treatment for AIP in China is limited and monolithic, and more attention needs to be paid to the treatment.